2000
DOI: 10.3758/bf03212114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time intervals and tone durations on auditory stream segregation

Abstract: Adult listeners rated the difficulty of hearing a single coherent stream in a sequence of high (H) and low (L) tones that alternated in a repetitive galloping pattern (HLH-HLH-HLH ...). They could hear the gallop when the sequence was perceived as a single stream, but when it segregated into two substreams, they heard H-H-... in one stream and L-L-... in the other. The onset-to-onset time of the tones, their duration, the interstimulus interval (lSI) between tones of the same frequency, and the frequency sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 11 publications
8
84
2
1
Order By: Relevance
“…As noted earlier, some patients may not have exerted much attentional focus during the task at presentation rates of 2000 ms ISI. On the other hand, rapidly presented stimuli could create an auditory streaming effect in which patients might only have to detect deviant "pop-outs" from the tone stream (Alain & Woods, 1993;Bregman et al, 2000;Fishman et al, 2004). Though patients would be under more time pressure to respond quickly at short ISIs, the increased streaming effect may facilitate deviant detection at fast stimulus rates, thus potentially weakening attentional effects.…”
Section: Causes Of Observed Disparities Between Intracranial and Scalmentioning
confidence: 99%
“…As noted earlier, some patients may not have exerted much attentional focus during the task at presentation rates of 2000 ms ISI. On the other hand, rapidly presented stimuli could create an auditory streaming effect in which patients might only have to detect deviant "pop-outs" from the tone stream (Alain & Woods, 1993;Bregman et al, 2000;Fishman et al, 2004). Though patients would be under more time pressure to respond quickly at short ISIs, the increased streaming effect may facilitate deviant detection at fast stimulus rates, thus potentially weakening attentional effects.…”
Section: Causes Of Observed Disparities Between Intracranial and Scalmentioning
confidence: 99%
“…The FB is affected only slightly by the repetition period of the tones, while the TCB increases markedly with increasing repetition period [2]. Bregman et al [18] showed that the most important temporal factor influencing the TCB was the time interval between successive tones of the same frequency (e.g. between the A tones in the sequence ABA-ABA), rather than the interval between tones of different frequency or the duration of the tones.…”
Section: The Build-up Resetting and Decay Of Stream Segregation (A)mentioning
confidence: 99%
“…1, panel b), where the underscore represents a silent gap. Starting with Miller and Heise (1950), numerous psychoacoustical studies have been performed using these types of tone sequences (e.g., van Noorden, 1975;Bregman, 1978;Bregman et al, 2000; for a review see: Bregman, 1990;Moore and Gockel, 2002;Carlyon, 2004). One basic result is that, depending on the frequency separation between the A and B tones, the stimulus can evoke two fundamentally different percepts.…”
Section: Introductionmentioning
confidence: 99%